Study of the Relationship Pattern of Ecdysis with Age of Freshwater Lobster Cherax quadricarinatus Aged 76 Days - Arif Habib Fasya (Central Research Institute For Agriculture, 2021)
The purpose of this study was to determine the pattern of LAT ecdysis especially the Freshwater Lobster of the Cherax quadricarinatus type, aged 76 days to 116 days. The purpose of this study was to determine the pattern of LAT ecdysis, especially the Freshwater Lobster of the Cherax quadricarinatus type, aged 76 days to 116 days. This research was conducted at the Experimental Station for Freshwater Aquaculture Sumber Pasir, Faculty of Fisheries and Marine Sciences, Universitas Brawijaya from July to August 2007. The method used in this study was a descriptive method in which this research gave an accurate description of an individual or group. Data collection techniques by way of direct observation. Then the data were analyzed statistically using the SPSS computer program version 11.5 for windows. Using simple linear regression analysis Crustacean growth is related to molting. In crustaceans, changes in shape and size can only occur if the hard calcareous exoskeleton is removed before the new cuticle hardens. Periodic molting or ecdysis continues by separating the old cuticle from the new instar, holding water absorption through the digestive tract, which is a characteristic of the Crustacea group as well as other aquatic insects. Then, the absorbed water is gradually replaced by biosynthesized protein, this growth process takes place continuously, the molting cycle can be divided into four stages, namely: proecdysis, ecdysis, metecdysis and intermoult.